Implementing the Visual-Auditory-Kinesthetic-Tactile (VAKT) Multisensory Approach in Indonesian Phonics Instruction for Slow Learners in Inclusive Early Childhood Education - Ratnasari Dwi Ade Chandra; Akhmad Dzukaul Fuad; Wisnu Kristanto (Journal of Childhood Development, 2026)
This study examines how the Visual-Auditory-Kinesthetic-Tactile (V-A-K-T) multisensory method plays out in Indonesian phonics instruction for slow learner children in inclusive early childhood education. Using a descriptive qualitative approach, it explores the learning process, teachers' strategies, and children's responses during phonics lessons at PAUD institutions in Jember Regency. Participants included the principal, classroom teachers, special assistant teachers, and slow learner children involved in phonics activities. Data were gathered through classroom observation, in-depth interviews, and documentation, then analysed using Miles and Huberman's interactive model of data reduction, display, and conclusion drawing. The findings show that V-A-K-T supported children's ability to recognize letters, identify letter sounds, and connect sounds to meaningful words. Learning activities included tracing letters in sand, shaping letters from plasticine, phonics songs, flashcards, alphabet posters, and movement-based games tied to vocabulary. The multisensory approach lifted children's participation, focus, confidence, and enthusiasm, and children responded well to interactive, concrete learning because it let them absorb visual, auditory, kinesthetic, and tactile input at once. The study also surfaced real challenges around preparation time, media availability, and individualized support, but overall found V-A-K-T an effective way to support phonics instruction for slow learners in inclusive early childhood education.